2001
DOI: 10.1046/j.0022-202x.2001.01442.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Non-Dividing Subpopulation of Mouse and Human Epidermal Cells Exhibiting High Levels of Persistent Ultraviolet Photodamage

Abstract: The distribution and persistence of cyclobutane pyrimidine dimers were investigated in mouse skin after chronic and acute exposures to ultraviolet-B radiation. We found that DNA damage accumulated in response to chronic irradiation and persisted in a unique set of epidermal cells located at the basal layer. Treatment with a tumor promoter caused the heavily damaged epidermal cells to divide and p53-immunopositive clusters to form within 24 h suggesting that these cells may be progenitors of the mutant p53 clus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 16 publications
2
40
2
Order By: Relevance
“…UVB exposure is known to be causative for erythema and pigmentation to wrinkling and elastosis in the skin. It is also demonstrated that sun light is associated with skin cancer and melanoma in humans (3,14,23). As shown in Table 2, in consistent with many previous studies, UVB-irradiation cannot cause the formation of DNA lesions, which are a primary factor in the development of skin cancer in mice (4,17).…”
Section: Discussionsupporting
confidence: 72%
“…UVB exposure is known to be causative for erythema and pigmentation to wrinkling and elastosis in the skin. It is also demonstrated that sun light is associated with skin cancer and melanoma in humans (3,14,23). As shown in Table 2, in consistent with many previous studies, UVB-irradiation cannot cause the formation of DNA lesions, which are a primary factor in the development of skin cancer in mice (4,17).…”
Section: Discussionsupporting
confidence: 72%
“…delayed recruitment of PCNA, pol h and gH2AX, indicating that retarded or incomplete repair of UV photolesions in normal cells also activates the DDR. Human skin epidermis from healthy individuals accumulates non-dividing basal cells that contain high levels of unrepaired damage (Mitchell et al, 2001). The accumulation of DNA damage might be due to differences in the expression of repair genes in these epidermal cells.…”
Section: Ape1 Initiates a Ddr In Non-dividing Repair-deficient Cellsmentioning
confidence: 99%
“…The number of photoproducts in epidermal DNA was determined by a radioimmunoassay as described previously (Mitchell et al, 1999). Briefly, the (6-4)PD antisera were raised against DNA that was irradiated with 100 kJ/m 2 UVC radiation (254 nm) to induce (6-4)PDs and CPDs.…”
Section: Dna Repair and Radioimmunoassaymentioning
confidence: 99%
“…Double hemizygous mice were mated to each other and resultant wild-type, E2f1 À/À , p53 À/À and double E2f1 À/À p53 À/À knockout mice were used for experiments. For all experiments, 6-to 8-week-old mice were UVB-irradiated with 12 Westinghouse FS20 sunlamps in an irradiation chamber of our design and manufactured to maximize fluence uniformity (Starch Art, Smithville, TX, USA) (Mitchell et al, 1999). According to the manufacturer's specifications, the broadband range for the UV lamps is between 280 and 400 nm, with 80% of the light in the UVB region, and 20% in the UVA region, with a peak wavelength at 297 nm.…”
Section: Animals and Uv Radiation Treatmentsmentioning
confidence: 99%